The generation of diversity in antibody genes - Neuberger, Michael (Henry Stewart Talks, 2007)
Historical perspective on antibodies and immunity, Nature and structure of antibodies and immunoglobulin fold, Theories of antibody formation, Clonal selection theory, Mechanisms contributing to antibody diversity, Organization of immunoglobulin loci, Immunoglobulin gene rearrangement and generation of the primary repertoire, RSS elements, RAG genes and mechanism of V-D-J joining, Membrane immunoglobulin and the B-cell antigen receptor, Secondary antibody repertoire and diversification of rearranged immunoglobulin genes, Affinity maturation, Somatic hypermutation, gene conversion and class-switch recombination, DNA deamination as a central trigger for these three diversification processes, Detailed pathways of antibody gene diversification, AID and the evolution of DNA deamination